MANAJEMEN LAYANAN TEKNOLOGI INFORMASI PADA PT PARAGON TECHNOLOGY AND INNOVATION - Fenny Purwani; Rendy Febriyana; Tiara Meftahul Jannah; Duwi Febyanti; Cica serioktawa; Marlingga Marlingga (CV. Denasya Smart Publisher, 2025)
This study aims to examine the implementation of IT service management based on the ITIL framework at PT Paragon Technology and Innovation, a prominent Indonesian cosmetics company leveraging information technology across its operations. A case study method was employed to describe the actual application of IT infrastructure, the IT service lifecycle, and role distribution through the RACI model. The findings reveal that PT Paragon has adopted most ITIL processes, particularly in incident management, system testing, and cloud-based infrastructure monitoring. The RACI model has been effectively utilized to define responsibilities across departments. This study recommends enhancing information security systems and fully adopting the Continual Service Improvement (CSI) framework.